Survival of COVID-19 patients research trends 2020-2022: a bibliographic study - Riadi, Dela; Trihandini, Indang (BKM Public Health and Community Medicine, 2022)
Purpose: With a bibliography analysis, this study attempted to reveal research trends in COVID-19 patient's survival from 2020-2022. Furthermore, it attempted to determine keyword co-occurrences and the bibliographic coupling of countries and sources. Understanding the trends within research on COVID-19 patients' survival is essential, and analysis might provide some information. Methods: Patients who had COVID-19 survived, based on the Scopus database. All articles could be stored in the research information system (.ris) and comma-separated values (CSV) versions. Using Microsoft Excel and the VOSviewer, analysis data mapping was accomplished. Results: The analysis's results show that during the period of three years, there have been various changes in the development of papers regarding the Survival of COVID-19 patients. It was determined that research on this subject increased from 2020 to 2021 but declined from 2021 to 2022 in the time from 2020 to 2022. The studies were composed by Tang N. (top publication), Li Y. (top author by document), and Chen X. Participants were published mainly in the USA (top country), PLOS One (top source). The keyword "human" comes the most (1730), while "covid-19" is the author's keyword (1281). There are many 304 total occurrences for the survival keyword. The strongest connections for collaborations occur between China and the United States, and for source, between Frontiers in Immunology and the Journal of Clinical Medicine. Conclusion: The COVID-19 patient's research survival in the years 2020–2022, however, was largely dependent on US-China collaboration. The Publication of Clinical Medicine and Frontiers in Immunology had the strongest association, per the co-author source, even though PLOS One was the most widely used journal for COVID-19 patients' survival studies. Research on COVID-19 patients' survival shows a decline in 2022.